ANALISIS SISTEM FONOLOGI KOSA KATA BENDA BAHASA JEPANG - Irma Winingsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2010)
This research is aimed at analyzing the phonological system of Japanese nouns in Minnano Nihongo 1. The analysis is based onsteps proposed by Masnur Muslich. There were 13 consonants and 10 vowels found. The result shows that there are 31 suspicious pairs, 14 pairs in segmental ananlogous environment, 4 pairs in suprasegmental environment, and 16 pairs in identical environment. Through the Uniting Procedure Analysis, 2 suspicious pairs are found: [e] as phoneme and [i] as allophone. In addition, the suspicious pairs of [o] and [u] function as phoneme and allophone respectively.Key words: Consonants, Japanese nouns, phonological system,suspicious pairs